PAST AND PRESENT EDUCATION IN UZBEKISTAN - Mirzayeva Zilola Mirjon qizi; Zubaydova Nilufar Negmatullayevna; Azzamova Nigora Rajabboyevna (TADQIQOTLAR.UZ, 2024)
Abstract: This article provides not only information about past and present education but also differences between last and current education in Uzbekistan. It describe research in the field of education and favorable opportunities. Besides this school textbooks are explained as examples.